TRUE-AMPLITUDE SEISMIC IMAGING - Protasov M.I.; Cheverda V.A. (My University, 2006)
The objective of our paper is to compute images of reflecting–scattering elements in the investigated geological medium for a given velocity model, i.e., for a model that describes the traveltime of waves with a sufficient degree of accuracy. At present, many approaches exist for computing wave images. All of them can be divided into two main (kinematic and dynamic) families. In our work, we shall deal with the dynamic approach. We shall be interested in the procedures for computing the images in true amplitudes, i.e., in amplitudes whose realizations are used to compute images free of the influence of the overlying strata and the system of perturbation and recording (illumination conditions).